The association of silicosis severity with pectoralis major muscle and subcutaneous fat volumes and the pulmonary artery/aorta ratio evaluated by CT - Yılmaz Çankaya, Bahar (Diagn Interv Radiol, 2021)
PURPOSE: Silicosis is an incurable occupational disease that sometimes rapidly progresses with fatal outcomes. We aimed to evaluate the association between disease severity and the change in the pectoralis major muscle volume (PMV), subcutaneous fat volume (SFV), and the pulmonary artery/aorta (P/Ao) ratio in patients with silicosis using computed tomography (CT). METHODS: The study included 41 male silicosis patients and 41 control group subjects with available chest CT images. Using dedicated software, we measured PMV and SFV from the axial CT images. We calculated the P/Ao ratio and obtained body mass index (BMI) and forced expiratory volume/forced vital capacity (FEV1/FVC) results from hospital records. We used the chest X-ray profusion score according to the International Labor Organization (ILO) classification to evaluate the severity of the silicosis. RESULTS: The mean age was 33.5±4.4 and 34.7±4.7 years in the silicotic and control groups, respectively. The mean BMI, PMV, SFV, and P/Ao values significantly differed between the study and control groups (p = 0.0009, p < 0.0001, p < 0.0001, and p = 0.0029, respectively). According to the ILO classification, there were 12 silicosis patients in category 1, 13 in category 2, and 16 in category 3. A significant difference was found between disease categories in terms of PMV, SFV, P/Ao, BMI, and FEV1/FVC values (p = 0.0425, p = 0.0341, p = 0.0002, p = 0.0492, and p = 0.0004, respectively). CONCLUSION: Disease severity had a stronger association with decreased PMV and SFV and increased P/Ao ratios than BMI in patients with silicosis caused by denim sandblasting. Thus, CT evaluation might be a useful indicator of disease severity.